2020
DOI: 10.1371/journal.pone.0233789
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane depletes macrophages from the melanoma microenvironment

Abstract: BackgroundWith more than 18 million annual new cases, cancer belongs to the major challenges of modern healthcare. Surgical resection of solid tumours under general anaesthesia is the prime therapy. Different aspects of anaesthesia are under discussion to independently influence the long-term outcome of cancer patients. Most recently, the commonly used volatile anaesthetics like sevoflurane have entered the spotlight, as retrospective studies suggest a detrimental outcome in certain cancer aetiologies with spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Sevoflurane (Sev) as a volatile anesthetic which is commonly used in clinical operations has been recently reported to exert antitumor physiologic effects in several tumors, including breast cancer ( 18 ), lung cancer ( 19 ), and colon cancer ( 20 ). Accumulating evidence has indicated that Sev exerts suppressive effects on the proliferation and metastasis of glioma cells in different molecular mechanisms, including suppressing Rac1/paxillin/FAK and Ras/Akt/mTOR in several tumor cells ( 21 ), regulating the ANRIL/let-7b-5p axis ( 22 ), and depleting macrophages from the melanoma microenvironment ( 23 ). Sev could also inhibit glioma cell proliferation and metastasis through the miRNA-124-3p/ROCK1 axis ( 24 ), KCNQ1OT1/miR-146b-5p/STC1 axis ( 25 ), miR-34a-5p/MMP-2 axis ( 26 ), and circ_0002755/miR-628-5p/MAGT1 axis ( 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sevoflurane (Sev) as a volatile anesthetic which is commonly used in clinical operations has been recently reported to exert antitumor physiologic effects in several tumors, including breast cancer ( 18 ), lung cancer ( 19 ), and colon cancer ( 20 ). Accumulating evidence has indicated that Sev exerts suppressive effects on the proliferation and metastasis of glioma cells in different molecular mechanisms, including suppressing Rac1/paxillin/FAK and Ras/Akt/mTOR in several tumor cells ( 21 ), regulating the ANRIL/let-7b-5p axis ( 22 ), and depleting macrophages from the melanoma microenvironment ( 23 ). Sev could also inhibit glioma cell proliferation and metastasis through the miRNA-124-3p/ROCK1 axis ( 24 ), KCNQ1OT1/miR-146b-5p/STC1 axis ( 25 ), miR-34a-5p/MMP-2 axis ( 26 ), and circ_0002755/miR-628-5p/MAGT1 axis ( 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the regulation of macrophages by anesthetics is not always beneficial to the body in disease progression. The use of sevoflurane is associated with reduced Tumor-associated macrophages (TAMs) and tumor growth in some cancer models ( Sztwiertnia et al, 2020 ).…”
Section: Macrophages and Anestheticmentioning
confidence: 99%
“…Dexmedetomidine and propofol inhibit the expression of lipopolysaccharide (LPS)-stimulated high mobility group box 1 (HMGB1) in macrophages ( Chang et al, 2013 ; Jia et al, 2017 ). The volatile anesthetic sevoflurane modulates macrophage recruitment, polarization, differentiation, apoptosis and pyroptosis by regulating the caspase-1, reactive oxygen species (ROS), forkhead box O1 (FoxO1), p21, and glycogen synthase kinase-3 (GSK-3β)/nuclear factor-E2-related factor 2 (Nrf2) pathways, which are involved in local immunity and tumor growth ( Jin et al, 2013 ; Fu et al, 2020 ; Sztwiertnia et al, 2020 ; Cai et al, 2021a ). Opioids, such as morphine, also inhibit the phagocytosis of macrophages and are associated with the reduction of macrophage colony-stimulating factor-induced proliferation and differentiation ( Sacerdote et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…They found isoflurane treatment did not upregulate HIF-1α and HIF-2α expression in RCC4-EV cells under 20% O 2 conditions, and further studies confirmed that isoflurane also did not affect the expression of genes associated with cancer hallmarks. 72 Therefore, the inhibitory effect of isoflurane on tumor angiogenesis still needs to be verified in different tumor types.…”
Section: Isofluranementioning
confidence: 99%